Interplay of Acquired Risk Factors, Age, and Genetic Predisposition in Incident Stroke: A Prospective Cohort Study - Yu‐Biao Wu; Ze‐Gui Huang; Wan‐Bing He; Si You; Shao‐Ling Zhang; Yang‐Wei Cai; Yuan‐Li Meng; Qing‐Yuan Gao; Jing‐Feng Wang; Hai‐Feng Zhang; Jing‐Wei Gao; Pin‐Ming Liu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Stroke is the leading cause of disability and death worldwide, and its pathogenesis involves various risk factors. This study aimed to investigate the associations between acquired risk factors, age, and genetic predisposition in the incidence of stroke. Methods and Results We analyzed 404 873 participants (age, mean±SD, 56.46±8.10 years; 45.97% men) from the UK Biobank cohort, all without a history of stroke at baseline and with complete information on risk factors. Hazard ratios and population‐attributable risk percentages for incident stroke were calculated for 21 risk factors, including 3 social determinants, 8 unhealthy behaviors, 4 metabolic factors, 5 clinical comorbidities, and 1 genetic risk score. Participants were stratified by age and genetic risk. During a 4.8 million person‐year follow‐up, 8287 participants (2.05%) experienced a stroke. Metabolic factors, particularly hypertension, were key contributors to stroke risk across all age and genetic groups (population‐attributable risk percentages, 26.53–38.63 and 28.05–37.09). Stroke risk due to overall metabolic factors increased with higher genetic risk (population‐attributable risk percentages, 28.05 in low‐risk and 37.09 in high‐risk groups). The effects of certain risk factors, such as dietary risk and hypertension, were more pronounced in participants with higher genetic risk. The contributions of social factors and clinical comorbidities to stroke risk were relatively low across genetic risk groups. Conclusions Metabolic factors, especially hypertension, are critical targets for stroke prevention across diverse age and genetic risk profiles. Tailored prevention strategies that address modifiable risk factors, considering individual age and genetic predisposition, have the potential to significantly reduce stroke incidence.